2018
DOI: 10.2298/fil1819713k
|View full text |Cite
|
Sign up to set email alerts
|

Cartesian product graphs and k-tuple total domination

Abstract: A k-tuple total dominating set (kTDS) of a graph G is a set S of vertices in which every vertex in G is adjacent to at least k vertices in S; the minimum size of a kTDS is denoted γ ×k,t (G). We give a Vizing-like inequality for Cartesian product graphs, namelywhere ρ is the packing number. We also give bounds on γ ×k,t (G H) in terms of (open) packing numbers, and consider the extremal case of γ ×k,t (Kn Km), i.e., the rook's graph, giving a constructive proof of a general formula for γ×2,t(Kn Km).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…We first remark the following Vizing-like inequality for the packing number proved by Kazemi et al [17]. That is, for all graphs G and H, ρ(G H) ≥ ρ(G)ρ(H).…”
Section: Cartesian Product Of Graphsmentioning
confidence: 88%
“…We first remark the following Vizing-like inequality for the packing number proved by Kazemi et al [17]. That is, for all graphs G and H, ρ(G H) ≥ ρ(G)ρ(H).…”
Section: Cartesian Product Of Graphsmentioning
confidence: 88%
“…The double total domination number has been well studied by the research community. For instance, in [1,4,17,19,21,22], some combinatorial results were presented, and in [2,3,18,23], some studies on certain product graphs were carried out. Our goal is to making some new remarkable contributions to this domination parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In [9] it was shown that the domination number can be also bounded from above by the packing number multiplied by the maximum degree of a graph. The inequality for the packing number of Vizing conjecture type was proven in [13].…”
Section: Introductionmentioning
confidence: 99%